Strategi Pengembangan Ekonomi Mualaf di Kota Padang - M. Zaky Mubarak Lubis (JURNAL ILMIAH SYI'AR, 2019)
This study aims to find the economic development strategies of converts in the city of Padang. The research approach was conducted using a descriptive qualitative method by collecting data through interviews, documentation and focus group discussions. The research explains that the economic problems of converts to cities in the city are caused by the severance of family relations, lack of ability, lack of converts, lack of assistance and lack of community awareness. The strategy in the economic development of converts in the city of Padang is happy with four processes. First, the making of converts as a means of gathering converts and becomes problem solving for all converts in the city of Padang. Second, capacity building is carried out by conducting trainings that provide theability of converts so that converts have the opportunity to make a business. Third, the provision of financial assistance aims to enable the ability of entrepreneurs who have been trained to be implemented in the form of business through financial assistance from both the government and the private sector. Fourth, supervision and assistance to the business carried out by converts in order to survive and be developed so that they can help other converts. To see the effects of the concept of this strategy it is necessary to implement all of these strategies so that they can be assessed and evaluated in an effort to improve the economy of converts.